212k views
2 votes
How do I solve the function:

Given f(x) = 5x − 7 and
g(x) = 11x − 1, solve for (g - f)(x).

User Picard
by
5.6k points

1 Answer

7 votes

Answer:

6x + 6

Step-by-step explanation:


(g-f)(x) is equal to
g(x)-f(x). So, the question is asking for you to subtract the given functions in that order. We know that
g(x) = 11x-1 and
f(x) = 5x-7. Thus, take the values of those functions and subtract them:


g(x) - f(x)\\= (11x-1)-(5x-7)\\= 11x-1-5x+7\\=6x+6

Thus, the answer is 6x + 6.

User Exoon
by
4.9k points